Effect of post-heat treatment on fire retardant treated wood properties - Özkan, Osman Emre; Temiz, Ali; Tor, Önder; Vurdu, Hasan (Walter de Gruyter GmbH, 2022)
Abstract In this study, Anatolian black pine (Pinus nigra subsp. pallasiana) was treated with fire retardants of 10, 20, and 30% aqueous solutions composed of di-ammonium phosphate (DAP), borax, boric acid, and glucose to determine the effectiveness of these chemicals in preventing the spread of fire. The treated wood was subjected to post-heat treatment at 120, 150, and 180 °C for 1 h to examine the effects of the post-heat treatment on pH changes, anti-swelling efficiency, water absorption, mechanical strength, accelerated weathering, leaching resistance, thermogravimetric analysis (TGA), UL-94 vertical burning test and crystallinity index. The post-heat treatment of fire-retardant treated wood reduced water intake and increased dimensional stability, while also improving mechanical and thermal properties in general. DAP/glucose complexes promote phosphorus fixation in wood and reduce leaching, resulting in long-term fire protection of wood in service. Because of these improvements in the post-heat treated wood by impregnated fire retardant, it can potentially be used as a reliable engineering material in a wide range of structural applications.